Development and validation of a two-dimensional pseudorandom balance perturbation test - Wagner, Andrew R.; Chirumbole, Sophia G.; Caccese, Jaclyn B.; Chaudhari, Ajit M. W.; Merfeld, Daniel M. (Frontiers in Human Neuroscience, 2024)
IntroductionPseudorandom balance perturbations use unpredictable disturbances of the support surface to quantify reactive postural control. The ability to quantify postural responses to a continuous multidirectional perturbation in two orthogonal dimensions of sway (e.g., AP and ML) has yet to be investigated.MethodsWe developed a balance perturbation paradigm that used two spectrally independent sum of sinusoids signals (SoS1, SoS2), one for each orthogonal dimension of tilt (roll and pitch), to deliver a two-dimensional (2D) balance perturbation. In a group of 10 healthy adults we measured postural sway during 2D perturbations, as well as for each of the two individual 1D perturbation components.ResultsWe found that during 2D perturbations, spectral peaks in the sway response were larger at the perturbed frequencies when compared to (1) the adjacent non-perturbed frequencies and (2) the frequencies contained within the orthogonal, spectrally independent perturbation signal. We also found that for each of the two spectra (SoS1, SoS2), the magnitude and timing of the sway response relative to the platform disturbance was similar when measured during 1D and 2D conditions.DiscussionThese data support that our novel 2D SoS perturbation test was able to evoke ML and AP postural responses that were (1) specific to the roll and pitch perturbations, respectively, and (2) similar to the responses provoked by individual 1D perturbations.